PR1P, a VEGF-stabilizing peptide, reduces injury and inflammation in acute lung injury and ulcerative colitis animal models - Adini, Avner; Ko, Victoria H.; Puder, Mark; Louie, Sharon M.; Kim, Carla F.; Baron, Joseph; Matthews, Benjamin D. (Frontiers in Immunology, 2023)
Acute Respiratory Distress Syndrome (ARDS) and Ulcerative Colitis (UC) are each characterized by tissue damage and uncontrolled inflammation. Neutrophils and other inflammatory cells play a primary role in disease progression by acutely responding to direct and indirect insults to tissue injury and by promoting inflammation through secretion of inflammatory cytokines and proteases. Vascular Endothelial Growth Factor (VEGF) is a ubiquitous signaling molecule that plays a key role in maintaining and promoting cell and tissue health, and is dysregulated in both ARDS and UC. Recent evidence suggests a role for VEGF in mediating inflammation, however, the molecular mechanism by which this occurs is not well understood. We recently showed that PR1P, a 12-amino acid peptide that binds to and upregulates VEGF, stabilizes VEGF from degradation by inflammatory proteases such as elastase and plasmin thereby limiting the production of VEGF degradation products (fragmented VEGF (fVEGF)). Here we show that fVEGF is a neutrophil chemoattractant in vitro and that PR1P can be used to reduce neutrophil migration in vitro by preventing the production of fVEGF during VEGF proteolysis. In addition, inhaled PR1P reduced neutrophil migration into airways following injury in three separate murine acute lung injury models including from LPS, bleomycin and acid. Reduced presence of neutrophils in the airways was associated with decreased pro-inflammatory cytokines (including TNF-α, IL-1β, IL-6) and Myeloperoxidase (MPO) in broncho-alveolar lavage fluid (BALF). Finally, PR1P prevented weight loss and tissue injury and reduced plasma levels of key inflammatory cytokines IL-1B and IL-6 in a rat TNBS-induced colitis model. Taken together, our data demonstrate that VEGF and fVEGF may each play separate and pivotal roles in mediating inflammation in ARDS and UC, and that PR1P, by preventing proteolytic degradation of VEGF and the production of fVEGF may represent a novel therapeutic approach to preserve VEGF signaling and inhibit inflammation in acute and chronic inflammatory diseases.